2016
DOI: 10.1016/j.jns.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Partial pharmacologic blockade shows sympathetic connection between blood pressure and cerebral blood flow velocity fluctuations

Abstract: Cerebral autoregulation (CA) dampens transfer of blood pressure (BP)-fluctuations onto cerebral blood flow velocity (CBFV). Thus, CBFV-oscillations precede BP-oscillations. The phase angle (PA) between sympathetically mediated low-frequency (LF: 0.03-0.15Hz) BP- and CBFV-oscillations is a measure of CA quality. To evaluate whether PA depends on sympathetic modulation, we assessed PA-changes upon sympathetic stimulation with and without pharmacologic sympathetic blockade. In 10 healthy, young men, we monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…At a group level, key findings indicated transient post-injury impairments in the capacity of the cerebrovasculature to buffer BP oscillations occurring at 0.10 Hz, the timescale over which sympathetic contributions to CA are thought to operate ( 24 , 28 ). At a within-subject level, more substantial impairments in CA were related with poorer performance on the SAC, a brief cognitive screen for concussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a group level, key findings indicated transient post-injury impairments in the capacity of the cerebrovasculature to buffer BP oscillations occurring at 0.10 Hz, the timescale over which sympathetic contributions to CA are thought to operate ( 24 , 28 ). At a within-subject level, more substantial impairments in CA were related with poorer performance on the SAC, a brief cognitive screen for concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence points to the importance of sympathetic innervation in the dynamic regulation of BP variability ( 51 ). Recently, pharmacological studies in healthy young adults have characterized sympathetic modulation of CA, whereby sympathetic activation has been shown to reduce both Phase and Gain at frequencies including 0.10 Hz, with even partial sympathetic blockade completely eliminating the Phase response ( 24 , 28 ). In accordance with the suggestion that progressive impairment of autoregulation likely first affects the latency of the response ( Phase ) before affecting the efficiency ( Gain ) ( 52 ), we observed significant changes in Phase only.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the RoR as an index of the dCA in the MCA and PCA was unchanged during CPT. In contrast to these results, Hilz et al [34] reported that CPT impaired the dCA in the MCA. One possible reason for this inconsistent result is that the foot was stimulated rather than the hand for the CPT.…”
Section: Discussionmentioning
confidence: 78%